Obsessive-Compulsive Inventory – Revised (OCI-R): Applicability to general population. - Malpica, María J.; Ruiz, Víctor M.; Godoy, Antonio; Gavino, Aurora (Anales de Psicología / Annals of Psychology, 2009)
The Obsessive-Compulsive Inventory - Revised (OCI-R; Foa et al., 2002) has became the measure of election for the assessment of obses-sive-compulsive behaviors, given its validity and the short time that its administration requires. Nevertheless, the OCI-R not yet has been studied on samples from the general population. In the present study the psycho-metric properties of the Spanish version of the OCI-R in two groups of subjects have been analyzed: university students (n = 247), which will allow comparing the results with those of previous studies, and general population (n = 395), which will allow generalizing these results to people without known clinical pathology or with subclinical symptoms. The factorial structure, the reliability and the convergent, divergent and crite-rion validity of the OCI-R were analyzed. The results show a factorial structure and psychometric properties of the Spanish version of the OCI-R similar to the ones found on the original version and, as expected, mod-erate relationship between the OCI-R scores and related variables: intru-sions, dysfunctional beliefs, worry, and perfectionism. It is concluded that the Spanish version of the OCI-R is applicable to the general population.